2022
DOI: 10.1371/journal.pone.0266175
|View full text |Cite|
|
Sign up to set email alerts
|

Predictors of post-COVID symptoms in Egyptian patients: Drugs used in COVID-19 treatment are incriminated

Abstract: Objectives COVID-19 is a multisystem disease, and some patients suffer from physical or psychological symptoms for weeks or even months after infection, which is described as post-COVID syndrome. The goal of this study is evaluating the prevalence of post-COVID-19 symptoms among Egyptian patients and detecting the factors associated with the presence of these symptoms. Methods An on-line cross-sectional survey using Google Forms was used to conduct the present study, which took place between June and August … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
4
17
0
Order By: Relevance
“…Our findings were the opposite from those reported by Peghin et al ( 18 ), who found no association between age and PCS symptoms after COVID-19. A previous study performed in the Middle East has pointed to female gender as a risk factor for PCS ( 19 ), suggesting a possible relation with Arabic culture, as females are used to take care of family members when they are infected. On the other hand, a relatively significant increase in PCS symptoms among females in UK suggests a possible biological relationship ( 20 ).…”
Section: Discussionmentioning
confidence: 98%
“…Our findings were the opposite from those reported by Peghin et al ( 18 ), who found no association between age and PCS symptoms after COVID-19. A previous study performed in the Middle East has pointed to female gender as a risk factor for PCS ( 19 ), suggesting a possible relation with Arabic culture, as females are used to take care of family members when they are infected. On the other hand, a relatively significant increase in PCS symptoms among females in UK suggests a possible biological relationship ( 20 ).…”
Section: Discussionmentioning
confidence: 98%
“…The probability of post covid syndrome symptoms, antiviral and anticoagulant therapy was significantly associated with persistence of COVID-19 symptoms. This is expected as these drugs are prescribed for severe and critical cases (26) .…”
Section: Resultsmentioning
confidence: 96%
“…We found that severity of index COVID-19 illness (SOFA scores or intubation) was a predictor of limited activities of daily living and post-acute COVID-19 symptoms. Indeed, many others have identified index COVID-19 severity as a predictor of protracted COVID symptoms [ 28 , 36 , 37 , [47] , [48] , [49] , [50] ]. Some studies have suggested that the severity of acute respiratory failure, rather than the pathogen involved, predicts neuropsychiatric sequelae.…”
Section: Discussionmentioning
confidence: 99%